Views______By This River - RACZYŃSKI, ALEKSANDER (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Presented pictures are part of longer series. They were taken in many different places. My photographs help me to understand the world and myself. I do not follow any specific topic but I do believe in being able to communicate without it. My life and my photography are both a constant confrontation with my emotions. They make me feel closer to my soul and to the nature. I find it very helpful as what scares me the most is the lack of emotions.